Process and property of hot-rolled stainless steel/carbon steel cladding bar - Zhining Jia; Yanan Gao (Functional Materials, 2016)
To study the process and property of hot-rolled stainless steel/carbon steel cladding bar, a rational pass system is designed for rolling and the bonding strength between the stainless steel cladding and carbon steel core was investigated by using shearing test and bending test. Then, the bonding interface, element diffusion and shearing fracture surface were analyzed by applying optical microscope, EDS and SEM. The results show that the thickness distribution of stainless steel shell is homogeneous; the metallurgical bonding between the two metals is formed after the third pass rolling and the shearing strength of the interface is more than 307 MPa. At the same time, the bending property of the bar displays well. The interface region is clearly divided into stainless steel zone, transition zone and carbon steel zone. Element diffusion occurs at the interface that the Fe of carbon steel diffuses into stainless steel and the Cr, Ni, Mn of stainless steel diffuse into carbon steel. It makes the formation of the transition zone with 20 μm in width in carbon steel and the total width of diffusion zone is 30 μm. Shearing strength of the interface after the sixth pass rolling is higher than the carbon steel substrate and the shearing fracture occurs in the carbon steel.